1982
DOI: 10.1111/j.1651-2227.1982.tb09521.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of an Automatic Oscillometric Method and of Various Cuffs for the Measurement of Arterial Pressure in the Neonate

Abstract: We compared simultaneous measurement of aortic, direct (Dir) and of indirect (Ind) systolic (S), mean (M) and diastolic (D) arterial pressure (AP) determined by an automatic oscillometric instrument (DINAMAP) in neonates with birthweight of 1000-3680 g. DINAMAP measurements were performed with cuffs of increasing width and length, recommended by the manufacturer for increasing arm circumference, and with a Standard sized cuff (2.5 X 15 cm), previously considered as suitable for neonates of any body size. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0
2

Year Published

1985
1985
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 10 publications
1
15
0
2
Order By: Relevance
“…In previous studies, it has been observed that smaller cuff size has been associated with NBP and UAC measurement discrepancies for all blood pressure parameters. 8,11 Although we found a similar association, the overall predictive value of cuff size, even when combined with other variables, was low (r 2 <0.3). Cuff location was not associated with NBP and UAC measurement discrepancies, with a large majority of NBP measurements obtained from the lower limbs.…”
Section: Blood Pressure Measurements In Elbw Infantsmentioning
confidence: 67%
See 2 more Smart Citations
“…In previous studies, it has been observed that smaller cuff size has been associated with NBP and UAC measurement discrepancies for all blood pressure parameters. 8,11 Although we found a similar association, the overall predictive value of cuff size, even when combined with other variables, was low (r 2 <0.3). Cuff location was not associated with NBP and UAC measurement discrepancies, with a large majority of NBP measurements obtained from the lower limbs.…”
Section: Blood Pressure Measurements In Elbw Infantsmentioning
confidence: 67%
“…Previous studies included both term and a mixed population of small and large preterm infants. [6][7][8]12 In these studies, NBP measurements generally correlated with arterial measurements, with the correlation coefficients for mean blood pressure ranging from 0.67 to 0.92. In a cohort of 12 very-lowbirth-weight infants, NBP measurements overestimated blood pressure, especially at the lower end of the blood pressure range.…”
Section: Blood Pressure Measurements In Elbw Infantsmentioning
confidence: 88%
See 1 more Smart Citation
“…Quando as medidas são realizadas em condições inapropriadas, o resultado pode ser 20 a 30% maior que o valor normal. Se isso ocorrer, recomenda-se repetir a avaliação e, se possível, utilizar a média de 3 ou mais medidas 4,6 . Deve-se utilizar também um manguito de tamanho adequado, já que manguitos menores que os recomendados podem determinar valores falsamente elevados e vice-versa 1,4,5,7,21 .…”
Section: Discussionunclassified
“…No início deste século, Balard já citava que a oscilometria era o único método que possibilitava a determinação da PA em crianças pequenas 4 . Atualmente, está comprovada a correlação entre a variação da PA determinada pela técnica de oscilometria e aquela obtida por cateter intra-arterial 1,[4][5][6][7] . Sendo assim, a oscilometria constitui um instrumento de grande utilidade para a monitorização não-invasiva de pacientes graves e para determinação da PA no exame detalhado do RN.…”
Section: Introductionunclassified